"This Condition isn't Going to get any Better so I can't see why we're Prolonging it": Risks and Benefits of using Empirical Research to Inform Normative Decisions Concerning End-of-Life Care. (3rd July 2018) - Fistein, Elizabeth; Clarke, Gemma; Holland, Anthony; Barclay, Stephen
Abstract: Progressive neurological diseases are often complicated by declining cognitive function (leading to impaired decision-making capacity) in addition to the physical impairments which have significant emotional and social consequences. Options for managing the later stages vary from invasive medical procedures, palliative care, and (in some jurisdictions) assisted suicide or euthanasia. Decisions about the right approach to take may be influenced by facts about the likely effectiveness of treatment. However, moral questions, such as the right balance between preserving life and maximizing quality of life, are an inherent part of the care-planning process. This paper takes nutritional support as an example of one area of decision-making that needs to be addressed during care-planning for people with progressive neurological disease. It describes research into the way in which the values of practitioners, members of the public and people with lived experience of progressive neurological disease may influence their decision-making about the right approach to maintaining nutritional intake during end -of-life care; and discusses some of the challenges of incorporating such findings into normative frameworks.